1969
DOI: 10.1037/h0028101
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of "real life" assessments of management potential with situational exercises, paper-and-pencil ability tests, and personality inventories.

Abstract: The major component of evaluation from a 2-day assessment program covering 47 members of a large national marketing organization consisted of ratings of degree of active participation in the group situational exercises, followed by ratings of administrative and decision-making ability Paper-and-pencil ability tests and personality inventories were less clearly related to assessments of managerial potential. Ratings of management potential developed from a careful review of company personnel records were as hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 11 publications
3
28
0
1
Order By: Relevance
“…Past empirical research suggests that management's ratings from the assessment center, along with the management evaluations of promotion potential, are important tools to predict employees' promotion and advancement in the organization (Hinrichs, 1969;1978). Recently, there has been an increasing trend for large corporations to dedicate efforts to the HiPo assessment and development (Church, Rotolo, Ginther, & Levine, 2015).…”
Section: Identification Of Hipo Employees and Challengesmentioning
confidence: 99%
“…Past empirical research suggests that management's ratings from the assessment center, along with the management evaluations of promotion potential, are important tools to predict employees' promotion and advancement in the organization (Hinrichs, 1969;1978). Recently, there has been an increasing trend for large corporations to dedicate efforts to the HiPo assessment and development (Church, Rotolo, Ginther, & Levine, 2015).…”
Section: Identification Of Hipo Employees and Challengesmentioning
confidence: 99%
“…First, compared to other selection tools, development and implementation costs, both financially and in amount of time spent, of using case-files are relatively low (Ash, et. al., 1989;Hinrichs, 1969). Next, the amount of effort expended on the part of both managers who make selection decisions and job candidates is considerably less than most paper-and-pencil testing systems or assessment centers (Ash, et.…”
Section: Case-based Decisionsmentioning
confidence: 99%
“…Finally, several studies have found that case-file information is a good predictor of future work performance when interpersonal factors are not important (Brown, 1991;Hinrichs, 1969;Lowry, 1994).…”
Section: Case-based Decisionsmentioning
confidence: 99%
See 2 more Smart Citations